Docking Of Protein With Flavonoids. - Ng, Pei Ling; Mohamed, Nomisah; Wahab, Habibah A.; Adnan, Rohana (2003)
Flavonoids are a group of potyphenots widely occurring in colorful pigment for fruits,vegetables and herbs (Lee, et. al.2OOO). Quercetin is one of the major components of flavonoids.